Hidden champions: a review of the literature & future research avenues - Julian Schenkenhofer (Management Review Quarterly, 2022)
Substantial efforts have contributed to overcome the scarcity of research on hidden champions. Nevertheless, literature has yet missed to compile a comprehensive review. Drawing on the insights of 112 publications, four strands of literature could be distinguished to unravel the essence of hidden champions. Research on hidden champions studies their (1) internationalization strategies, (2) R&D and innovation strategies, the (3) worldwide and regional geographic distribution of hidden champions and finally (4) other research that could not be assigned to one of the first three strands. A hand-collected sample of 1372 German hidden champions exemplifies the key insights from the reviewed research articles. Discussing the findings of the different literature strands aims at drawing a conclusion on their main results and analytical pitfalls to eventually unfold and motivate future research avenues.
Keywords: D4; L1; L22; O32; 650; Literature review; Hidden champions; Niche strategy; Mittelstand; Family firms